Variations in surgical technique for adrenalectomy with caudal vena cava venotomy in 19 dogs. Issue 5 (25th January 2019) - Knight, Rebekah C.; Lamb, Christopher R.; Brockman, Daniel J.; Lipscomb, Victoria J.
Abstract: Objective: To describe surgical techniques, caval occlusion times, and short‐term outcomes in dogs undergoing adrenalectomy with caval venotomy. Study design: Retrospective case series. Animals: Dogs undergoing adrenalectomy with caval venotomy between October 1, 2010 and May 31, 2018. Methods: Medical records of dogs undergoing adrenalectomy with caval venotomy were reviewed for signalment, perioperative management, surgical details, perioperative complications, mortality, and histopathology. Computed tomography images were reviewed to describe tumor morphology and signs of thrombus extension. Results: Nineteen dogs had adrenal tumor thrombi extending into the prehepatic (14 dogs, 74%), hepatic (3 dogs, 16%), and posthepatic (2 dogs, 11%) caudal vena cava. Tumors occurred in left (11) and right (8) adrenal glands. Median caval occlusion was 6.5 minutes (range, 2–25). Two to six vascular tourniquets were used. Venotomy closure was performed under full caval occlusion in 11 dogs and by using a partial occlusion clamp in 8 dogs. Left ureteronephrectomy was performed in 5 dogs. Perioperative mortality rate was 21% (4 dogs). Conclusion: Extension of caval tumor thrombus beyond the hepatic hilus did not preclude a good outcome. Longer caval occlusion than has been previously reported was tolerated in some cases. Number of vascular tourniquets used reflected the location of phrenicoabdominal vein insertion on the cava and length of the caval tumor thrombus. Venotomy closure under full occlusion was often required for right adrenal tumors. When required, ureteronephrectomy was left sided. Clinical significance: Dogs with adrenal tumors extending beyond the hepatic hilus and those requiring a long caval occlusion time can survive adrenalectomy.